The house of trials - Juana Ines de la Cruz Sister, 1651-1695 (Iberica (New York, N.Y.) ;, 1996)
"First complete English translation of Sor Juana's brilliant comedia, Los empenos de una casa (1989), in which she subverts the conventions of gender and Golden Age drama to suit her own feminine perspectives. Castano, the male character disguised as a woman, performs the construction of gendered identity. Notes help with the 17th-century references and baroque Spanish. Bibliography of primary and secondary sources. This script served for premier productions in March 1996 at Oklahoma City Univ. and at the International Siglo de Oro Theater Festival in El Paso. The annotated translation is clear but its modern registers lose the baroque flavor and wit of the original, in contrast to Peden's translation"--Handbook of Latin American Studies, v. 58.